2007
DOI: 10.3748/wjg.v13.i4.633
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of colonic injuries following blunt trauma

Abstract: AIM:To retrospectively evaluate the preoperative diagnostic approaches and management of colonic injuries following blunt abdominal trauma. METHODS:A total of 82 patients with colonic injuries caused by blunt trauma between January 1992 and December 2005 were enrolled. Data were collected on clinical presentation, investigations, diagnostic methods, associated injuries, and operative management. Colonic injury-related mortality and abdominal complications were analyzed. RESULTS:Colonic injuries were caused mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 11 publications
2
29
0
8
Order By: Relevance
“…Bhatti et al recommended primary repair for the management of penetrating colonic injury because of its better outcome in terms of less infection and early recovery 4 . Zheng et al treated 81.7% patients with primary repair with 16% would infection 9 . Naraynsingh et al found 10% wound infection rate in their study to support the view of primary repair of colon to be the management of choice 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatti et al recommended primary repair for the management of penetrating colonic injury because of its better outcome in terms of less infection and early recovery 4 . Zheng et al treated 81.7% patients with primary repair with 16% would infection 9 . Naraynsingh et al found 10% wound infection rate in their study to support the view of primary repair of colon to be the management of choice 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Colon is one of the most commonly injured viscera followed by small gut and liver in abdomen for which management becomes complicated had the type and severity of injury not been assessed properly 4,5 . In primary repair of wound, researchers used several options of primary repair with or without colostomy to check the effectiveness of repair without diversion [6][7][8][9][10][11][12][13][14] . Similar types of intervention had been adopted in developing countries too [15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang YX et al (14) in their retrospective study reported the degree of peritoneal fecal contamination as the only independent predictor of complications. The location of the colon injury as an important risk factors for anastomotic leak is controversial.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…A positive test is defined as evidence of free fluid or solid organ parenchymal injury. 16 DPL was the diagnostic method of choice for evaluating blunt abdominal injury in the past, but recently has been often replaced by CT imaging. 17 DPL is an important adjunct in cases where bowel injury is suspected.…”
Section: Total 13mentioning
confidence: 99%